FEMME FATALE AND THE BODY MOTIF IN MACEDONIAN WOMEN'S POETRY (Philological Studies, 2025)
The figure of the deadly, fatal woman or femme fatale has always appeared in world literature and culture. This is especially the case in poetry, which is interwoven with physicality, touch and heightened sensuality, because the female body is the main attribute of the femme fatale. That motif is also present in Macedonian female poetry, such as in the poetry of Svetlana Hristova-Jocikj, Katica Kjulavkova and Liljana Dirjan. It is the analysis of their poems that represents the main interest of this work, in order to show how the femme fatale motif is expressed in their poetic work and in what way it is connected to the female body, eros, touch and sensuality. Each individual poetess has her own specific creative procedures and ways in which she profiles the character of the femme fatale and weaves it into her verses, thereby giving it a voice to speak. In the poetry of Svetlana Hristova-Jocikj, we can highlight two main archetypes of the femme fatale; Mother Earth and Wild Woman. In the verses of Katica Kjulavkova, a high concentration of eros, physicality and touch comes to the fore. In the poetry of Liljana Dirjan, it is definitely necessary to emphasize its deep sensuality and, above all, a kind of identification of love sensuality with gastronomic pleasures.
Keywords: Poetry, Femme Fatale, Body, Macedonian female poetry, Female archetypes